Influence of the drying mode of support on the properties of Pd/Al2O3–ZrO2 materials used for methane combustion - C. Amairia; S. Fessi; M. Mhamdi; A. Ghorbel; J. Llorca (Scientific Reports, 2023)
Abstract This work constitutes a new trial to enhance the properties of palladium supported on alumina modified with zirconium used as catalysts for methane combustion. The effect of the support drying mode is studied. For this aim, Al2O3-ZrO2 binary oxides with zirconium loading of 2 and 5% in weight were prepared using sol–gel process then dried under ordinary or supercritical conditions. Palladium with a loading of 0.5% was deposited on the support by wet impregnation. Several techniques have been used to investigate differences between the two types of the derived catalysts.